2014
DOI: 10.1186/2193-1801-3-523
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac taurine and principal amino acids in right and left ventricles of patients with either aortic valve stenosis or coronary artery disease: the importance of diabetes and gender

Abstract: Free intracellular taurine and principal α-amino acids (glutamate, glutamine, aspartate, asparagine and alanine) are abundant in human heart. They are cellular regulators and their concentration can change in response to disease and cardiac insults and have been shown to differ between hypertrophic left ventricle (LV) and the relatively "normal" right ventricle (RV) in patients with aortic valve stenosis (AVS). This difference has not been shown for coronary artery disease (CAD) and there are no studies that h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 57 publications
0
17
0
Order By: Relevance
“…Also, low plasma levels of taurine have been reported in patients with diabetic cardiomyopathy (Franconi et al 1995(Franconi et al , 2004. It has also been reported by Lewis et al (2014) that the increase in metabolic stress induces a decrease in myocardial taurine. Such cardiac metabolic stress leads to the development of necrosis, hypertrophy, and heart failure.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…Also, low plasma levels of taurine have been reported in patients with diabetic cardiomyopathy (Franconi et al 1995(Franconi et al , 2004. It has also been reported by Lewis et al (2014) that the increase in metabolic stress induces a decrease in myocardial taurine. Such cardiac metabolic stress leads to the development of necrosis, hypertrophy, and heart failure.…”
Section: Introductionmentioning
confidence: 88%
“…The beneficial effects of taurine have been demonstrated in many diseases such as decreased serum low-density lipoprotein, decreased progression of atherosclerosis, and protection against ischemiareperfusion injury of the myocardium (Schaffer and Kim 2018;Xu et al 2008;Abebe and Mozaffari 2011;Lambert et al 2015;De Luca et al 2015). Besides, the beneficial effects of taurine in diabetic cardiovascular complications are well documented (Franconi et al 1995(Franconi et al , 2004Inam-U-Llah et al 2018;Lewis et al 2014;Manna et al 2013;Tappia et al 2011Tappia et al , 2013Tappia et al , 2018Turan 2010). It has been suggested that taurine increases the high-energy phosphate content of the heart (Schaffer and Kim 2018;Schaffer et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Studies on the determination of taurine and a number of amino acids predominant in the myocardium (glutamate, aspartate, glutamine and asparagine) in coronary insufficiency showed their differences in the content in the left and right ventricles in coronary insufficiency. A comparison of the levels of these amino acids in aortic stenosis and coronary heart disease in myocardial biopsy specimens showed higher concentrations of taurine in the left ventricle in both situations [34]. With severe, progressive cardio sclerosis in the rabbit myocardium, the content of phenylalanine and tyrosine increased, which was also found in patients with coronary heart disease, and the degree of increase in the level of amino acids changed depending on the clinical forms of coronary atherosclerosis (angina pectoris of various functional classes, myocardial infarction).…”
mentioning
confidence: 95%
“…It takes an active part in the metabolism of carbohydrates, fats and amino acids, the activation of antioxidant and detoxifying systems. Methionine serves as an essential precursor of cysteine, glutathione, and taurine and, as a cysteine precursor, is involved in the synthesis of insulin and coenzyme A. Methylation processes (involving S -adenosylmethionine) are associated with gene expression, the functioning of the sympathoadrenal system, and the formation of choline and acetylcholine [34].…”
mentioning
confidence: 99%
“…It takes an active part in the metabolism of carbohydrates, fats and amino acids, the activation of antioxidant and detoxifying systems. Methionine serves as an essential precursor of cysteine, glutathione, taurine and, as a cysteine precursor, is involved in the synthesis of insulin and coenzyme A. Methylation processes (involving Sadenosylmethionine) are associated with gene expression, the functioning of the sympathoadrenal system, and the formation of choline and acetylcholine [34].…”
mentioning
confidence: 99%